Analysis of The Use of Chinese Degree Adverbs by Indonesian Students - Diana Constansz Sahertian (Makassar State University, 2023)
Abstract. Degree adverbs are one of the important and difficult learning points in Teaching Chinese as a second language (TCSL). Commonly, Chinese degree adverbs are divided into two types and four levels. Each type and level have different collocations, semantic features, etc. According to the academic article collections in CNKI and google scholar, research on Chinese degree adverbs from the perspective of TCSL for Indonesian students is still very limited. This study discusses the use of Chinese degree Adverbs by Indonesian students. This study aims to describe the student selection of Chinese degree adverbs and to find the most frequent error types in using four commonly used comparative degree adverbs: low-level ‘shaowei’, medium-level ‘bijiao’, high-level ‘geng’, and extreme-level ‘zui’. The approach to this study is a quantitative-qualitative method. The samples are Chinese Department students at one of the universities in Bandung city. The data was collected from two exercises. This study applies the error analysis procedure introduced by McDowell to find the most frequent error types. The result shows that the students tend to use pure degree adverbs, and the most used pure degree adverb is high-level ‘hen’, followed by its synonymous words ‘tebie’, ‘feichang’, ‘tai’, and ‘shifen’. In using synonymous degree adverbs, students tend to use the first learned word. The form of exercises in the teaching material should encourage the student to use more varied degree adverbs. The most frequent error types in using four different levels of comparative degree adverbs are selection in bijiao word sentences and zui word sentences, misordering of degree adverbs, and the omission of complement ‘yidianr/yixie’ in shaowei word sentences. The major cause of the errors is intralingual interference. This study made some suggestions for the improvement of Chinese degree adverbs teaching material based on the findings.Keywords: Chinese Degree Adverbs, Selection Tendencies, Frequent Error Types, Indonesian Students